2016
DOI: 10.3389/fphar.2016.00453
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP2C19 Variants on Clinical Efficacy of Clopidogrel and 1-Year Clinical Outcomes in Coronary Heart Patients Undergoing Percutaneous Coronary Intervention

Abstract: The impact of pharmacogenetic variants of cytochrome P450 2C19 (CYP2C19) on clopidogrel-mediated effects on platelet inhibition, inflammatory response and endothelial function, as well as risk of major adverse cardiovascular events (MACE), in coronary heart patients undergoing percutaneous coronary intervention (PCI) was investigated. To this end, we assessed the residual platelet aggregation rate (RPA), maximal aggregation rate (MAR) and plasma levels of sCD40L, sP-selectin, MMP-9, sVCAM-1 and sE-selectin aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Our data revealed that CYP2C19 *2 LOF alleles were associated with a higher risk of MACE compared with non‐LOF alleles [OR 2.571; 95% CI (1.143‐5.780), P = 0.030]. Sun et al reported that the risk of MACE in CYP2C19 metabolizers was 2.664 times higher than in noncarriers. Clopidogrel is activated by CYP2C19 and it then irreversibly inhibits the P2Y 12 subtype of ADP receptor .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Our data revealed that CYP2C19 *2 LOF alleles were associated with a higher risk of MACE compared with non‐LOF alleles [OR 2.571; 95% CI (1.143‐5.780), P = 0.030]. Sun et al reported that the risk of MACE in CYP2C19 metabolizers was 2.664 times higher than in noncarriers. Clopidogrel is activated by CYP2C19 and it then irreversibly inhibits the P2Y 12 subtype of ADP receptor .…”
Section: Discussionmentioning
confidence: 57%
“…However, poor metabolizers could influence the pharmacokinetics of clopidogrel, resulting in inaccessible and impaired antiplatelet effect as well as reduced clinical effect . Preliminary data demonstrated that genetic variants may influence the metabolism of clopidogrel, presumably leading to individual clinical effect of platelet inhibition …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MEA, multiple electrode aggregometry; LTA, light transmission aggregometry; PRU, platelet reactive units; HPR, high platelet reactivity; LPR, low platelet reactivity. is known that PM among Asian patients may experience better efficacy with a higher clopidogrel dose via the potential reduction of the incidence of major adverse cardiovascular events (MACE) [17]. Indeed, the elevated risks of MACE may be attributed to the specific CYP2C19 genotypes causing higher residual platelet reactivity [18].…”
Section: Discussionmentioning
confidence: 99%
“…Clopidogrel is a prodrug and is transformed into the active metabolite H4 by several cytochrome P450 (CYP450) isoenzymes. A substantial number of clinical trials have observed that CYP450 genetic polymorphisms, especially the CYP2C19 loss-of-function ( CYP2C19 * 2 and CYP2C19 * 3 ) and/or gain-of-function ( CYP2C19 * 17 ) variants, can affect the antiplatelet efficacy of clopidogrel and the clinical outcomes (Chen et al, 2008a ; Paré et al, 2010 ; Zhang et al, 2015b , 2017 ; Sun et al, 2016 ). Evidences showed that the CYP2C19 intermediate metabolizers (IM, genotyped as CYP2C19 * 1 * 2 or CYP2C19 * 1/ * 3 ) and CYP2C19 poor metabolizers (PM, genotyped as CYP2C19 * 2/ * 2, CYP2C19 * 2/ * 3 , or CYP2C19 * 3 * 3 ) showed obviously increased risk of recurrence of ischemic events than CYP2C19 extensive metabolizers (EM, genotyped as CYP2C19 * 1 * 1 ) after PCI (Mega et al, 2010 ; Mao et al, 2013 ; Zhong et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%